Discriminant Subspace Low-Rank Representation Algorithm for Electroencephalography-Based Alzheimer’s Disease Recognition - Tang, Tusheng; Li, Hui; Zhou, Guohua; Gu, Xiaoqing; Xue, Jing (Frontiers in Aging Neuroscience, 2022)
Alzheimer's disease (AD) is a chronic progressive neurodegenerative disease that often occurs in the elderly. Electroencephalography (EEG) signals have a strong correlation with neuropsychological test results and brain structural changes. It has become an effective aid in the early diagnosis of AD by exploiting abnormal brain activity. Because the original EEG has the characteristics of weak amplitude, strong background noise and randomness, the research on intelligent AD recognition based on machine learning is still in the exploratory stage. This paper proposes the discriminant subspace low-rank representation (DSLRR) algorithm for EEG-based AD and mild cognitive impairment (MCI) recognition. The subspace learning and low-rank representation are flexibly integrated into a feature representation model. On the one hand, based on the model robustness of low-rank representation, the graph discriminant embedding is introduced to constrain the representation coefficients, so that the representation coefficients can preserve the local manifold structure of the EEG data. On the other hand, the least squares regression (LSR), principle component analysis (PCA) and global graph embedding are introduced into subspace learning, so as to make the model more discriminative. The objective function of DSLRR is solved by the inexact augmented Lagrange multiplier method. The experimental results show that the DSLRR algorithm has good classification performance, which is helpful for in-depth research on AD and MCI recognition.